Step 1: 5 x 2 = 10
Step 2: 10^6 x 10^-2 = 10^4
Step 3: 10^4 = 1 x 10^4
Step 4: 1 x 10^4 in Scientific Notation
Simplify this expression and put your answer in Scientific Notation: (5×10^6)×(2×10^−2)
(4 points)
Step 1: ____ the coefficients
Step 2: ____ the exponents to simplify.
Step 3: ____ to change the exponent for Scientific Notation
Step 4: ____ is the final answer.
3 answers
Step 1: 5 x 2 = 10^1 !!!
Step 2: 10^1 * 10^6 x 10^-2 = 10^5
Step 3: 10^5 = 1 x 10^5
Step 4: 1 x 10^5 in Scientific Notation
Step 2: 10^1 * 10^6 x 10^-2 = 10^5
Step 3: 10^5 = 1 x 10^5
Step 4: 1 x 10^5 in Scientific Notation
You are correct, it should be 10^1 instead of 10. Thank you for pointing that out.
The final answer is indeed 1 x 10^5 in Scientific Notation.
The final answer is indeed 1 x 10^5 in Scientific Notation.